NILAI-NILAI SOSIAL DALAM NOVEL JAWA PRAU GETHEK NYABRANG JALADRI KARYA IR. H. SOEKIRMAN: KAJIAN SOSIOLOGI SASTRA - Raihan Adib Ghifari (University of Brawijaya, 2025)
One of the Javanese literary works in the form of a novel is a novel entitled Prau Gethek Nyabrang Jaladri by Ir. H. Soekirman. This novel specifically discusses the life of Javanese society from the past to the present. The purpose of this research is to determine the social values ??and implied messages in the Prau Gethek Nyabrang Jaladri novel. This research uses a qualitative descriptive research method using the Sociology of Literature approach with the theory used, namely the Marxist Sociology theory. Based on the results of the research that has been carried out with the Marxist Sociology theory, several social values ??have been found in the Prau Gethek Nyabrang Jaladri novel. These social values ??include the values ??of divinity, family, culture, economy, and social life. In addition, an implied message has been found in this novel.